2022
DOI: 10.1080/22423982.2022.2037257
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempts among Greenlandic forensic psychiatric patients – prevalence and determinants

Abstract: This nationwide cross-sectional study of the lifetime prevalence and determinants of suicide attempts includes 90% of Greenlandic forensic psychiatric patients. Retrospective data were collected from electronic patient files, court documents, and forensic psychiatric assessments using a coding form from a similar study. We used unpaired t-tests and chi 2 or Fisher’s exact test. The lifetime prevalence of suicide attempts was 36% (n = 32), and no difference in prevalence was found between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Studies have shown that a series of variables were associated with suicide attempts, such as sex, grade, residence, family integrity, feeling meaningless in life, depression, bullying perpetrator, autonomy parenting, self-esteem, hopelessness, and stressful life events ( 5 ). Physical abuse in childhood, family history of substance misuse, and criminal convictions among family members might also play a role in affecting attempted suicide ( 25 ). However, these features were investigated among general adolescents but were not especially for predicting self-poisoning suicide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that a series of variables were associated with suicide attempts, such as sex, grade, residence, family integrity, feeling meaningless in life, depression, bullying perpetrator, autonomy parenting, self-esteem, hopelessness, and stressful life events ( 5 ). Physical abuse in childhood, family history of substance misuse, and criminal convictions among family members might also play a role in affecting attempted suicide ( 25 ). However, these features were investigated among general adolescents but were not especially for predicting self-poisoning suicide.…”
Section: Discussionmentioning
confidence: 99%
“…Validation of the nomogram was conducted using discrimination and calibration. Discrimination was the capacity to discriminate patients with and without the positive event (23, 24), and the metrics that used to evaluate discrimination mainly included area under curve (AUC) and discrimination slope. Calibration was defined as the consistency of the anticipated and observed probability of the positive event (23, 24), and the metrics mainly included Brier score, Brier scaled score, and Hosmer and Lemeshow test.…”
Section: Nomogram Development and Validationmentioning
confidence: 99%
“…Data in this retrospective cross-sectional study is part of a previous study of forensic psychiatric patients in Greenland. Data was collected on February 29th, 2020 [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…The majority of Greenlandic forensic psychiatric patients are treated as outpatients [ 28 ]. The Department of Psychiatry in Nuuk has twelve beds.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation